Mary Pope Osborne's Magic Tree House : Night of the Ninjas - Book 5 Night of the ninjas - Laird, Jenny, 1969-; Matthews, Kelly (Comic book artist); Matthews, Nichole; Osborne, Mary Pope. (New York : Random House, 2023)
"The magic tree house takes Jack and Annie back in time to feudal Japan where the siblings learn about the ways of the Ninja."--
Keywords: Annie -- (Fictitious character from Osborne) -- Comic books, strips, etc; Jack -- (Fictitious character from Osborne) -- Comic books, strips, etc; Annie -- (Fictitious character from Osborne) -- Fiction; Jack -- (Fictitious character from Osborne) -- Fiction; Time travel -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Tree houses -- Comic books, strips, etc; Ninja -- Comic books, strips, etc; Time travel -- Fiction; Magic -- Fiction; Tree houses -- Fiction; Ninja -- Fiction; Adventure and adventurers -- Fiction; Graphic novels; Japan -- Comic books, strips, etc. -- History; Japan -- Fiction. -- History; Graphic novels; Action and adventure comics; Time-travel comics; Comics adaptations; Comics (Graphic works)